Analysis of the “Deep Listening” Spiritual Pedagogy Approach in Online Learning to Build Intersubjectivity - Tacoh, Yuliana TB (Jurnal Ilmiah Peuradeun, 2023)
Online learning is often complained about as it makes students uncomfortable and inactive in learning activities because they need to meet face-to-face with classmates and teachers. This article explained how in the online learning model, students could feel involved with all learning components even if they were not face-to-face while using the “deep listening” spiritual pedagogy approach. The practice of “deep listening” pedagogy was carried out on students in the General Basic Course lecture class, namely Religious Education, with 35 students. The goal was to encourage student engagement and the ability to connect with all components in the learning classroom. Data were collected through observation and implementation of “deep listening” practice through focus group discussion, then analyzed with a qualitative approach. The result showed that through observation and practice of “deep listening” in the focus of online group discussions, 1) students could convey their inner voice openly and honestly. 2) It can be observed through conversations that there were changes in students’ perceptions about the meaning of beliefs, human nature, religious experiences, relationships with others, and the development of spirituality. 3) It can be observed that students’ ability to engage and feel connected to all components of learning was a meaning of intersubjectivity through opinions and thoughts conveyed in online learning.